Factors associated with menopausal age in Iranian women: Tehran Lipid and Glucose Study. Issue 4 (21st December 2012) - Farahmand, Maryam; Tehrani, Fahimeh Ramezani; Pourrajabi, Leila; Najafi, Masood; Azizi, Fereidoun
Abstract Aim Menopause, considered a special event in a woman's life, has a wide age range, 40–60 years, and there is no consensus regarding the factors influencing it. We aimed to assess factors affecting the menopausal age in a population of women participants of the Tehran Lipid and Glucose Study. Material and Methods For the present study, 1114 women were selected from among participants of the Tehran Lipid and Glucose Study. Following implementation of our inclusion criteria, their reproductive histories and demographic background as well as anthropometric parameters were assessed, and ordinal regression analysis was conducted using spss version 15. Results The mean estimated age at menopause ± standard deviation was 49.6 ± 4.5 years. Menopausal age was considerably lower among women with a history of smoking (P = 0.05), and it increased with increasing age of menarche (P = 0.04) and number of children (P = 0.05). There was no significant correlation between the mean age of menopause and the educational level and anthropometric parameters. Conclusion The smoking status, parity and the age of menarche are the influencing factors of age at menopause among the Iranian population.